Enabling Cyber Physical Systems with Wireless Sensor Networking Technologies. (22nd May 2012) - Lin, Chih-Yu; Zeadally, Sherali; Chen, Tzung-Shi; Chang, Chih-Yung
Abstract : Over the last few years, we have witnessed a growing interest in cyber physical systems (CPSs) that rely on a strong synergy between computational and physical components. CPSs are expected to have a tremendous impact on many critical sectors (such as energy, manufacturing, healthcare, transportation, and aerospace) of the economy. CPSs have the ability to transform the way human-to-human, human-to-object, and object-to-object interactions take place in the physical and virtual worlds. The increasing pervasiveness of wireless sensor networking (WSN) technologies in many applications makes them an important component of emerging CPS designs. We present some of the most important design requirements of CPS architectures. We discuss key sensor network characteristics that can be leveraged in CPS designs. In addition, we also review a few well-known CPS application domains that depend on WSNs in their design architectures and implementations. Finally, we present some of the challenges that still need to be addressed to enable seamless integration of WSN with CPS designs.